Entangled far rights : a Russian-European intellectual romance in the Twentieth Century - Laruelle, Marlène (Series in Russian and East European studies., 2018)
Since the rise of Putin, many have puzzled by the strange affinity of the far right in the West for today's authoritarian Russia. Entangled Far Rights explores the deep roots of this phenomena and reveals it to be a running thread through the entire history of the long 20th century and present regardless of the changing political character of Russia's regimes.